Optimal Design of Elastic Arches with I Cross-Section - Szefer, G.; Mikulski, L. (Engineering Transactions, 1984)
This paper concerns strength optimization of elastic arches with I cross-section. Arches are subjected to a dead weight and useful external load. The volume of the element or the deflection at the chosen point are the optimality criteria. Side conditions concern strength constraints (bending and shearing stress) and geometry is imposed on the dimensions of the cross-section. The effective Pontryagin method is used for solving the formulated tasks of optimization. The computer program has been designed and particular solutions for various forms of the arch centre line and for various kinds of support have been obtained.